Effect of poly(methyl methacrylate) modified water hyacinth fiber on properties of low density polyethylene/ natural rubber/water hyacinth fiber composites - Supri, A. Ghani, Dr.; S. J, Tan; Hanafi, Ismail; Teh, Pei Ling (Taylor & Francis Group, 2011)
Link to publisher's homepage at http://www.tandfonline.com/